Strategic basin and delta planning increases the resilience of the Mekong Delta under future uncertainty - Schmitt, R J P; Giuliani, M; Bizzi, S; Kondolf, G M; Daily, G C; Castelletti, Andrea (Proceedings of the National Academy of Sciences - PNAS, 2021)
The climate resilience of river deltas is threatened by rising sea levels, accelerated land subsidence, and reduced sediment supply from contributing river basins. Yet, these uncertain and rapidly changing threats are rarely considered in conjunction. Here we provide an integrated assessment, on basin and delta scales, to identify key planning levers for increasing the climate resilience of the Mekong Delta. We find, first, that 23 to 90% of this unusually productive delta might fall below sea level by 2100, with the large uncertainty driven mainly by future management of groundwater pumping and associated land subsidence. Second, maintaining sediment supply from the basin is crucial under all scenarios for maintaining delta land and enhancing the climate resilience of the system. We then use a bottom-up approach to identify basin development scenarios that are compatible with maintaining sediment supply at current levels. This analysis highlights, third, that strategic placement of hydropower dams will be more important for maintaining sediment supply than either projected increases in sediment yields or improved sediment management at individual dams. Our results demonstrate 1) the need for integrated planning across basin and delta scales, 2) the role of river sediment management as a nature-based solution to increase delta resilience, and 3) global benefits from strategic basin management to maintain resilient deltas, especially under uncertain and changing conditions.